HIV/AIDS information needs of Grade 12 learners in Maseru - Mohale, Malume; De Wet, Johann C. (University of the Free State, 2003)
In this article a needs-based perspective is suggested for approaching communication about HIV/Aids. The argumentation is guided by two assumptions. The first is that HIV/Aids communication campaigns that do not take into account the information needs of target audiences are not likely to produce the desired impact. The second is that such campaigns are bound to fail if they are not informed by research which will help determine the needs, preferred mode of production, packaging as well as dissemination channels. Such research will also help evaluate the impact of campaigns on target audiences. These assumptions were validated in research focusing on determining the HIV/Aids information needs of Grade 12 learners living in Maseru, Lesotho. The main conclusion drawn from the results is that HIV/Aids campaigns that have been undertaken in Lesotho have tended to focus very little on the information needs of this target group.
Keywords: Maseru, Lesotho; HIV and AIDS; Information needs; Learners; Secondary education